Pulmonary Function Tests In Young Healthy Subjects Of North India - Rastogi, Parag; Tandan, H C; Saxena, Jalaj; Gupta, Sushma; Saxena, Sonali; Saha, Saurabh (Indian Journal of Community Health, 2004)
Study Objectives : The diagnosis of disease done by skiagram can be substantiated by pulmonary function tests. Substantial data of Indians on PFTs is not available. The present study therefore has been planned on young healthy north Indians. Setting : 119 males and 49 female medical students of North India. Measurements : PFT's, T.V. FEV1, FVC, FER and PEFR were measured. P<0.05 was considered as significant. Results : In North Indian males, mean T. V was 437.56 ± 65.83 ml, FEV1 3.26 ±041 L, FVC 3.82 ± 0.48 L, FER 85.09 ± 2.42% and PEFR was 495.42 ± 101.82 L / min. In North Indian females, average T. V was 386.12 ± 37.90 ml, FEV1 2.39 ± 0.38 L, FVC 2.79 ± 0.43 L, FER 85.38 ± 257% and PEFR was 307.12 ± 75.74 L / min. Conclusions: Males in comparison to females had more value of PFTs. All the PFTs showed positive correlation with Height, Weight and Surface area except Tidal Volume and FER.